State Liability for The Fault Causing Damage in Outer Space - Arnanda Yusliwidaka; Kholis Roisah; Joko Setiyono (JED (Jurnal Etika Demokrasi), 2023)
The implementation of outer space exploring and using activities by a state builds on the Space Treaty 1967. This provision governs two basic principles in using outer space: non-appropriation and freedom exploration. The principle of giving the states a freedom to do their activities in outer space leads so many space objects to be launched. Some problems then result from the activities done by the states in outer space: outer space debris problem, falling space object, and misuse.  If a state does an activity and then results in damage or loss against other stages in the outer space, it will be imposed with a liability as governed in the Liability Convention 1972. This research focuses on a study on the concept of state’s liability if its activities in outer space results in damage/loss against other states. This research used a normative legal research method, aiming to analyze the concept of fault from the state’s action resulting in damage/loss against other states in outer space. This analysis is important because the term of the fault of state action is not defined in Liability Convention 1972.